Student Acceptance of AI-Generated Feedback in Revising Argumentative Essays Among EFL Undergraduate Students - Zakaria Zakaria; Jumbuh Prabowo (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This study is about how students who are learning English as language use feedback from artificial intelligence when they edit essays that argue for something. The study also wants to find out what things affect how much these students use this feedback. The people who did the study used a way of doing things and they used a mix of numbers and talked to people to get their information. They worked with 30 students who are studying to teach English. These students had to write essays. Then edit them. The people who did the study looked at what the students changed in their essays. They also asked the students questions in surveys and in interviews. They used numbers to understand the information they got from the essays and the surveys. They used words to understand what the students said in the interviews. The students who are learning English as a language and the artificial intelligence feedback are very important to this study. The study is really about the English, as a foreign language student. How they use artificial intelligence feedback. According to the findings, most students were able to accept AI-generated feedback, especially when it came to language-related topics like grammar and vocabulary. The whole application category had the greatest uptake rate. On the other hand, adoption rates for argument development and idea organization were typically lower. Scores on the original and updated manuscripts increased significantly after utilizing statistical testing AI-generated feedback (p 0.05). Additionally, although they still had trouble comprehending conceptual feedback, students' opinions of AI use tended to be favorable. These results suggest that while AI-generated feedback is useful in raising the caliber of EFL students' writing, especially in linguistic areas, it still has limitations when it comes to fostering the growth of argumentation abilities. To get the results using artificial intelligence in teaching people how to write should always have help from teachers. The use of intelligence in writing education needs to have teachers assisting with the learning process. This way the use of intelligence in writing education will be really helpful.